Effect of dietary supplementation of ginger on feed conversion ratio, carcass physiognomies and haematological parameters in broiler - Mahdy, Md Sadik Al; Islam, Md Faridul; Hasan, Md Nakibul; Habib, Ashadul; Sikder, Mahmudul Hasan (Research in Agriculture Livestock and Fisheries, 2017)
This study evaluated the effect of ginger on the growth performance, carcass quality of broiler chickens. A total of 40 broiler chickens were randomly selected into four groups identified as A (1% ginger extract), B (2% ginger extract), C (positive control) and D (negative control). All groups contain equal number of birds (n=10.) Birds were treated with aqueous ginger extract via drinking water. Significant variations (p<0.05) existed between the control and other treatments in mean final body weight, dressed weight, daily feed intake and feed conversion ratio. At the end of experiment (35th day) for 1% ginger extraction treatment the live body weight is 1745gm (p<0.05), dressing weight 1135.3 (p<0.05) and FCR is 1.66 (p<0.05). The usage of the test ingredients had a significant effect (p<0.05) on dressing percentage. Administration of ginger to broiler chickens increased their performance, FCR as well as blood parameters. It is, thus, recommended in broiler chicken production alternative to antibiotic and/or growth promoter. Res. Agric. Livest. Fish.4(3): 173-179, December 2017